POLITICS AND THE CHALLENGES OF INTERNATIONAL LAW IN POST-COLONIAL NIGERIA - Goodluck Etinagbedia (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
The study examined the politics and the challenges of international law enforcement in post-colonial Nigeria as it relates to International Maritime/Environmental and Human Right law in Nigeria. The study made used of the Neo – realism theory as the intellectual frame-work and adopted the qualitative and synthesis of scientific method as its relies on secondary data collected from documentations through publish and unpublished books, journal, articles and other publications on Human Rights and maritime/Environmental treaties. The findings of the study revealed that the politics and practices of the Nigeria government with respect to implementation and enforcement of international law showed that Nigeria either lack the capacity or is unwilling to implement and enforce the provision of the policies and practices enshrined in these treaties. Based on these findings and the conclusion arising thereof, it is recommended hereby that training should be carried out for the bureaucracy and other relevant agencies to ensure effective implementation of the various international legal instruments that Nigeria is a signatory to.